1993
DOI: 10.1111/j.1600-0676.1993.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile and plasma lipid composition in non‐obese normo‐lipidemic subjects with and without cholesterol gallstones

Abstract: ABSTRACT— A two‐stage study was carried out to characterize the bile and plasma lipid composition in normolipidemic non‐obese patients with and without cholesterol gallstones. The first stage involved 11 patients with cholesterol gallstones admitted for elective cholecystectomy and a control group of 16 patients without cholesterol gallstones undergoing elective laparotomy. Bile samples were obtained intraoperatively by aspiration from the gallbladder. The bile of all the gallstone patients was supersaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Specifically, bile is rich in micelles, high, intermediate, low and very-low density lipoproteins, which are composed of varying proportions of triglycerides, phospholipids, cholesterol and amphipathic proteins42. Bile is also rich in branched-chain amino acids43 and long-chain saturated palmitic acid (C16:0) as well as unsaturated linoelaidic (C18:2) and arachidonic (C20:4) fatty acids44. In contrast, although O. viverrini uses glycolysis for energy production, bile is usually depleted of glucose45; thus, this fluke has evolved several adaptations to a life in bile (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, bile is rich in micelles, high, intermediate, low and very-low density lipoproteins, which are composed of varying proportions of triglycerides, phospholipids, cholesterol and amphipathic proteins42. Bile is also rich in branched-chain amino acids43 and long-chain saturated palmitic acid (C16:0) as well as unsaturated linoelaidic (C18:2) and arachidonic (C20:4) fatty acids44. In contrast, although O. viverrini uses glycolysis for energy production, bile is usually depleted of glucose45; thus, this fluke has evolved several adaptations to a life in bile (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because we found no considerable evidence for disease effects due to biliary stones, it is possible that high levels of triglycerides, and low levels of HDL and apo A, may affect the risk of biliary stones through their involvement in several key processes of gallstone pathogenesis. For example, high serum triglyceride levels are associated with increased cholesterol saturation of the bile 7,30,31 and rapid nucleation of cholesterol crystals, 32 important precursors to gallstones. Similarly, low serum levels of apo A have been linked to decreased cholesterol crystallization in the bile, 33 and low serum levels of HDL have been associated with increased biliary cholesterol saturation and bile acid hyposecretion, 8,[30][31][32] which reduces cholesterol solubility in the bile and leads to gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high serum triglyceride levels are associated with increased cholesterol saturation of the bile 7,30,31 and rapid nucleation of cholesterol crystals, 32 important precursors to gallstones. Similarly, low serum levels of apo A have been linked to decreased cholesterol crystallization in the bile, 33 and low serum levels of HDL have been associated with increased biliary cholesterol saturation and bile acid hyposecretion, 8,[30][31][32] which reduces cholesterol solubility in the bile and leads to gallstone formation. 34 Although the exact role of low levels of total cholesterol and/or LDL in gallstone formation is unclear, a number of indirect observations suggest a possible inverse association between total cholesterol and gallstone pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that high TG serum levels and low ApoA‐I, were significantly associated with an increased risk of biliary stones as well as excess risks of biliary tract cancers. They proposed several key processes of gallstone pathogenesis connecting the fact that high TG has been associated with increased cholesterol saturation of the bile and rapid nucleation of cholesterol crystals, important precursors to gallstones . Similarly, low serum levels of ApoA‐I have been linked to decreased cholesterol crystallization in the bile , and low serum levels of HDL have been associated with increased biliary cholesterol saturation and bile acid hyposecretion .…”
Section: Lipid Profile Associated With Several Types Of Cancermentioning
confidence: 99%